Interaction between "Accelerating-Packing" Flows in a Low-Temperature Gas - Gordevskyy, V. D.; Andriyasheva, N. V. (Журнал математичної фізики, аналізу, геометрії, 2009)
The Maxwellians of a special type, which correspond to inhomogeneous, nonstationary flows and describe the acceleration and packing of gas along some direction, are studied. The approximate description of interaction between these two flows for the model of hard spheres, when the temperatures are sufficiently small, is obtained in a form of bimodal distribution with various coefficient functions. Mathematics Subject Classification: 76P05, 45K05, 82C40, 35Q55.